Impact of Physical Training on Mitochondrial Respiratory Complex in Aging Skeletal Muscle - Kusuma, Lydia; Juhanna, Indira Vidiari (Sport and Fitness Journal, 2024)
There is an inverse relationship between age and muscle function, where both muscle strength and mass decline as an individual gets older. The gradual decline in both aspects can lead to mobility disabilities and premature mortality. The deterioration of skeletal muscle mitochondria is believed to be a major contributor to these events. Nevertheless, adopting approach such as regular physical training could slow down this deterioration in mitochondrial function and alleviate age-related effects in humans. This review proposes that physical training has the beneficial outcome on the function of mitochondria in the skeletal muscle of older adults.